2018
DOI: 10.1074/jbc.ra118.004862
|View full text |Cite
|
Sign up to set email alerts
|

Development of an allosteric inhibitor class blocking RNA elongation by the respiratory syncytial virus polymerase complex

Abstract: Respiratory syncytial virus (RSV) represents a significant health threat to infants and to elderly or immunocompromised individuals. There are currently no vaccines available to prevent RSV infections, and disease management is largely limited to supportive care, making the identification and development of effective antiviral therapeutics against RSV a priority. To identify effective chemical scaffolds for managing RSV disease, we conducted a high-throughput anti-RSV screen of a 57,000-compound library. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 62 publications
1
38
0
Order By: Relevance
“…A total of 141,936 compounds were screened for inhibitory activity against recHPIV3-JS NanoLuc (MOI = 0.2 TCID 50 units/cell). HTS was carried out analogous to our previous reports 64 , 73 , with automated reading of plates 30 hours after infection. Raw data were imported into the MScreen IT environment and analyzed using data mining tools developed in-house or build into the MScreen package as described 64 , 73 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 141,936 compounds were screened for inhibitory activity against recHPIV3-JS NanoLuc (MOI = 0.2 TCID 50 units/cell). HTS was carried out analogous to our previous reports 64 , 73 , with automated reading of plates 30 hours after infection. Raw data were imported into the MScreen IT environment and analyzed using data mining tools developed in-house or build into the MScreen package as described 64 , 73 .…”
Section: Methodsmentioning
confidence: 99%
“…HTS was carried out analogous to our previous reports 64 , 73 , with automated reading of plates 30 hours after infection. Raw data were imported into the MScreen IT environment and analyzed using data mining tools developed in-house or build into the MScreen package as described 64 , 73 . Hit candidates were defined as compounds with anti-HPIV3 active >2.66×SD in control-dependent mean percent inhibition calculation and >2.1×SD in control-independent mean robust z-score calculation.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of these pan-resistance sites suggests that it may be challenging to proactively counteract viral escape through synthetic scaffold optimization [69]. Supporting this notion, a large-scale high-throughput drug screen using a recombinant RSV strain carrying a signature pan-resistance mutation did not return any hits blocking F protein activity, although entry inhibitors typically emerge readily and are often pharmacodominant in anti-RSV drug screens [70,71]. Secondly, studies in the mouse RSV pathogenesis model have demonstrated early that signature pan-resistance mutations such as F D401E do not mandatorily coincide with viral attenuation in vivo [68], raising substantial concern that entry inhibitor-resistant RSV may emerge rapidly in the field, and remain pathogenic and possibly able to spread.…”
Section: Synthetic F Protein Blockersmentioning
confidence: 99%
“…Alternatively, allosteric and substrate-analog inhibitors of the RSV polymerase complex have been identified [70,[101][102][103][104][105], some of which likewise showed promising drug-like properties and potently blocked virus replication in cell culture and in vivo. Ultimately, the therapeutic targeting of the polymerase may be more fruitful for two main reasons [106]: (i) all enzymatic functions of the viral polymerase complex, initiation of RNA synthesis, RNA elongation, mRNA capping, and cap methylation, must be performed multiple times to complete an individual viral replication cycle, providing-in contrast to entry inhibition-repeated opportunities for interference, and (ii) polymerase blockers suppress not only the synthesis of structural virion components directly, but also heighten virus susceptibility to the innate host antiviral response, since they prevent the expression of viral non-structural immune-modulatory proteins that are essential for viral pathogenesis [107,108].…”
Section: Perspectives For Pneumo-and Paramyxovirus Entry Inhibitorsmentioning
confidence: 99%
“…hRSV is an enveloped, negative-sense, and single-stranded RNA virus that encodes 10 genes that are translated into 11 proteins (Figure 1) (23). Its replication and gene transcription occur in the cytoplasm, thanks to the aid of an RNA-dependent RNA-polymerase that is encoded within the viral genome by the L gene (24, 25). For its adequate function, the L protein requires the viral phosphoprotein P, which associates to this RNA polymerase (26, 27).…”
Section: Hrsv Genes and The Virion Structurementioning
confidence: 99%